PKM Pendampingan Penyusunan AD/ART BUMDes di Desa Kayutanyo Kecamatan Luwuk Timur Kabupaten Banggai - Faradina Dinda Sahala; Sena Arta Mefia; Randi Muhammad; Indra Prasetyo; Risman Jainahu; Wildan Zaman; Kisman Karinda (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of carrying out community service activities is to provide understanding to Kayutanyo village government officials in formulating legal documents that regulate the organizational structure, governance and business activities of BUMDES in accordance with statutory provisions. The implementation method is carried out by observation, coordination and implementation assistance. The results of the implementation of pkm activities related to the preparation of AD/ART can be concluded that to improve the village economy, Kayutanyo village has natural resources that can be utilized to increase village income. The role of BUMDes in managing the village's natural resource potential will influence the growth of village income and improve community welfare. The BUMDes Articles of Association/Regulations are guidelines, rules and regulations for the implementation of BUMDes activities. So the preparation of AD/ART requires good knowledge and understanding.